A rare presentation of post COVID-19 inflammatory aortitis - Hoi Yee Annie Lo; Pouria Parsa (Annals of Vascular Surgery - Brief Reports and Innovations)
The COVID-19 pandemic has affected over 60 million individuals globally, resulting in >15 million deaths. While the virus predominantly targets the respiratory system, it can also affect other organ systems, including the cardiovascular system. There have been limited reports on COVID-19-associated aortic pathology. We aim to contribute to the current literature by presenting the case of a 70-year-old female from Southern California with post-COVID-19 inflammatory aortitis.The patient, who had been diagnosed with COVID-19 without respiratory symptoms, initially presented with failure to thrive. A comprehensive workup revealed rapidly progressing penetrating aortic ulcers involving the ascending and descending thoracic aorta as well as the infrarenal abdominal aorta. Within two weeks, these ulcers evolved into saccular aneurysms measuring up to 4 cm. After evaluating surgical repair versus medical therapy, the patient and family collectively elected to pursue nonoperative management with high-dose pulse corticosteroids with close observation. Under this regimen, the aneurysms showed slight growth but remained below 6 cm, with no immediate need for surgical intervention.This case underscores the potential for life-threatening vascular complications of COVID-19 and highlights the importance of early recognition and individualized treatment strategies. As our understanding of COVID-19-associated vascular inflammation evolves, further studies are needed to refine management approaches and improve outcomes for affected patients.